PERBANDINGAN EFEKTIVITAS UAP AROMATERAPI LEMON DENGAN GINGER OIL TERHADAP EMESIS GRAVIDARUM DI TPMB EF TANGERANG BANTEN TAHUN 2022 - Budiasih, Siti; Rifiana, Andi Julia; Indrayani, Triana (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2023)
Emesis gravidarum is a common obstetric problem affecting 50-80% of pregnant women during the first trimester that begins in the morning and often continues throughout the day. If not treated effectively can cause complications in pregnancy that affect the quality of life, pregnancy and fetus. Emesis gravidarum can progress to Hyperemesis gravidarum, a condition characterized by excessive nausea and vomiting. Non-pharmacological therapy for emesis gravidarum is using aromatherapy steam of lemon oil and ginger oil. Lemon essential oil and ginger oil have long been known to be able to reduce complaints of emesis gravidarum because the content of lemon oil is linalyl and the main content of ginger oil is zingiberen which can provide a refreshing and warming effect which could reduce emesis gravidarum. to compare the effectiveness of aromatherapy lemon aromateraphy with ginger oil against emesis gravidarum at TPMB EF Tangerang Banten in 2022. This study used a quasi-experimental design with a two groups pretest- posttest approach. The data were analyzed using a paired sample t-test and an independent sample t-test to compare the effectiveness of aromatherapy steam before and after administration of lemon with ginger oil against emesis gravidarum using a questionnaire sheet. The results showed that there was a significant effect before and after giving lemon aromatherapy steam and ginger oil with a P Value = 0.000 and there was an effectiveness of giving lemon oil and ginger aromatherapy steam to emesis gravidarum with P Value = 0.000. There is a significant comparison between giving lemon oil aromatherapy steam and ginger oil to reducing emesis gravidarum. It is hoped that midwives can provide information about the benefits of lemon aromatherapy steam and ginger oil to pregnant women who experience emesis gravidarum Keywords: lemon oil, ginger oil, emesis gravidarum